2024
DOI: 10.1186/s12870-024-04782-6
|View full text |Cite
|
Sign up to set email alerts
|

Facultative mycorrhization in a fern (Struthiopteris spicant L. Weiss) is bound to light intensity

Thais Guillen-Otero,
Soon-Jae Lee,
Dietrich Hertel
et al.

Abstract: Background The establishment of mycorrhizal relationships between a fungus and a plant typically enhances nutrient and water uptake for the latter while securing a carbon source for the fungus. However, under a particular set of environmental conditions, such as low availability of light and abundant nutrients in the soil, the resources invested in the maintenance of the fungi surpass the benefits obtained by the host. In those cases, facultative mycorrhizal plants are capable of surviving with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 56 publications
4
13
0
Order By: Relevance
“…In our case, we trust the negative results for three reasons. First, in another fertilization study on ferns, using the same metabarcoding approach, we obtained clear differences in the fungal communities between nutrient treatments (Guillen-Otero et al, 2024), showing that the methods are suitable for detecting responses of root-associated fungi in ferns. Second, our analyses revealed clear and biologically meaningful differences between fern species and life forms, both for root-associated fungi and leaf nutrients, again confirming the suitability of the methods.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In our case, we trust the negative results for three reasons. First, in another fertilization study on ferns, using the same metabarcoding approach, we obtained clear differences in the fungal communities between nutrient treatments (Guillen-Otero et al, 2024), showing that the methods are suitable for detecting responses of root-associated fungi in ferns. Second, our analyses revealed clear and biologically meaningful differences between fern species and life forms, both for root-associated fungi and leaf nutrients, again confirming the suitability of the methods.…”
Section: Discussionmentioning
confidence: 79%
“…A: M. wolfii (F = 7.976, p < .001***). B: C. peladensis (F = 6.303, p < .01**), E. latifolium (F = 6.331, p < .001***), H. polyanthos (F = 0.694, p < .001***), and M. wolfii (F = 4.036, p < 0.05*).degree of mycorrhization in the temperate fern species Struthiopteris spicant was found to be strongly influenced by light availability (hence carbon limited), and not by nutrient availability (nutrient limited)(Guillen-Otero et al, 2024). Although this finding suggests that mycorrhization in ferns is not as linked to nutrient availability as it is in other vascular plant groups, there is still a need for more detailed studies to understand its nature and role in ferns.AUTHO R CO NTR I B UTI O N S M.K.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…However, the percentage of AMF presence is lower in ferns, at approximately 67% ( Lehnert et al., 2017 ). It has been suggested that the relatively low percentage of mycorrhization in ferns stems from limited photosynthetic capabilities, so that their growth may be more strongly limited by carbon rather than nutrients ( Kessler et al., 2014 ; Guillen-Otero et al., 2024 ). However, the majority of AMF research has been conducted on angiosperms, leaving ancient plant lineages like ferns poorly studied ( Pressel et al., 2016 ; Lehnert et al., 2017 ; Strullu-Derrien et al., 2018 ; Field et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In consequence, there is a lack of understanding of the fungal taxonomic diversity and their functionality in ferns ( Lehnert et al., 2017 ; Strullu-Derrien et al., 2018 ; Sandoz et al., 2020 ; Guillen-Otero et al., 2023 ). Moreover, while it is well known that fern communities are impacted by precipitation, resource availability, and temperatures, among other factors ( Kessler et al., 2011 ; Weigand et al., 2020 ), there is limited data related to the influence of environmental factors on fern-fungus interactions ( Lehnert et al., 2017 ; Sandoz et al., 2020 ; Weigand et al., 2022 ; Guillen-Otero et al., 2024 ). In seed plants, the distribution, composition, and abundance of their associated AMF communities has been found to be influenced by temperature, precipitation, light availability, soil vertical structure, pH and nutrient concentration, biotic interactions, and the host and the fungus genotypes ( Hodge et al., 2000 ; Öpik et al., 2006 ; Lekberg et al., 2007 ; Dumbrell et al., 2010b ; Liu et al., 2014 ; Shi et al., 2014 ; Tedersoo et al., 2014 ; Bennett and Klironomos, 2019 ; Větrovský et al., 2019 ; Neuenkamp et al., 2021 ; Peña Venegas et al., 2021 ; Han et al., 2024 ; Lekberg et al., 2024 ).…”
Section: Introductionmentioning
confidence: 99%